Simultaneous determination of dazomet and propanil by partial least squares (PLS-2) and zero-crossing derivative spectrophotometry methods - Turak, F.; Ozgur, M. Ustun; Ercag, A.; Bozdogan, A. (FREUND PUBLISHING HOUSE LTD, 2006)
Multicomponent analysis has become one of the most appealing topics for analytical chemists in the last few years. In recent years Partial Least Squares multivariate spectrophotometric calibration (PLS-2) and derivative spectrophotometry have been widely used for the resolution of binary and ternary mixtures and satisfactory results were reported. A simple and fast spectrophotometric method is proposed for the simultaneous determination of Propanil (P), and Dazomet (D) by means the partial least square treatment of the spectrophotometric absorbance data between 200 nm and 320 nm, taken at 5 nm intervals. The method involves the use of 9 standard mixtures of two compounds assayed, considered at three concentration levels and the measurement of the absorbance of samples in 75% ethanol in water solution. A computer program for PLS-2 was written according to the algorithm given by Marten and Naes. For the comparison of the results derivative spectrophotometric procedure (Zero-crossing technique) was used. In this method the D content was determined from the second derivative spectrum by measuring the signal at 284 nm (D-2(284)) (Zero-crossing point for P) and by using appropriate calibration graph. The P content was determined in the same way by measuring the signal at D-2(256.1) (Zero-crossing point for D). Calibration graphs were obtained between 2.0 - 6.0 mu g.ml(-1) for P and between 3.0-9.0 mu g.ml(-1) for D. When we used first derivative spectrum by measuring the signal at 262.5 nm and 286.9 nm for P and D respectively, we could measured 0.2-1.0 mu g.ml(-1) and 0.5-2.5 mu g.ml(-1) concentration level of D and P. The methods were checked by applying them to the analysis of laboratory prepared mixtures over the concentration ranges 2.0-6.0 for P, and 3.0-9.0 mu g.ml(-1) for D.
Keywords: derivative spectrophotometry; multivariate analysis; pesticides (dazomet, propanil); binary mixtures; PERFORMANCE LIQUID-CHROMATOGRAPHY; ACETYLSALICYLIC-ACID; TERNARY MIXTURES; SUNSET YELLOW; PONCEAU 4R; TABLETS; WATER; ACETAMINOPHEN; CALIBRATION; DRUGS; Chemistry